Preparation method of SSZ-13 molecular sieve
Through the one-step hydrothermal synthesis method, industrial perlite waste is directly mixed with other raw materials, hydrothermal crystallization is carried out, and SSZ-13 molecular sieve is prepared, which solves the problems of cumbersome pretreatment steps and high energy consumption in the existing technology, and achieves efficient and simplified zeolite molecular sieve synthesis.
Patent Information
- Application Number
- CN202411929838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art requires cumbersome acid activation, alkali activation or high-temperature calcination pretreatment when zeoliteizing industrial perlite waste, which increases energy consumption and step complexity.
A one-step hydrothermal synthesis method is used to directly mix the template agent, alkaline source, water, industrial perlite waste and silicon source, and hydrothermal crystallization is carried out to prepare SSZ-13 molecular sieve, and the pretreatment step is omitted.
It realizes efficient synthesis of SSZ-13 molecular sieves with high added value without pretreatment, simplifies the process flow, reduces energy consumption, and improves the crystallinity and purity of the product.
Smart Images

Figure CN119735217A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste resource utilization and molecular sieve synthesis, and in particular to a method for preparing SSZ-13 molecular sieve. Background Art
[0002] Zeolite molecular sieve is an important type of inorganic microporous aluminosilicate with regular pore structure, good thermal stability and modifiability. It is an important inorganic porous material with wide applications in petrochemical industry catalysis, small molecule adsorption and separation, heavy metal wastewater treatment, etc. So far, the International Zeolite Association (IZA) Structural Committee has collected more than 256 molecular sieves with different framework structure types.
[0003] Perlite is a naturally formed volcanic rock with a bound water content of 2-6%. It is mainly composed of quartz and alumina and is characterized by an amorphous structure. When rapidly heated to 870°C, the bound water of the perlite evaporates and forms an expanded structure, that is, expanded perlite. Expanded perlite can be used as a high-efficiency thermal insulation material with its high bulk density and vesicular structure. However, in the process of producing expanded perlite, some perlite powder cannot expand at high temperatures due to its small grain size (below 60 mesh), thus forming industrial perlite waste. These perlite wastes are highly volatile and difficult to store, and excessive stacking will cause environmental problems. Developing industrial perlite waste into high-value-added zeolite molecular sieves is of great significance for realizing the resource recycling of industrial perlite waste. However, at present, the zeoliteization of solid waste generally requires acid activation, alkali activation or high-temperature calcination pre-treatment steps to convert more of the silicon and aluminum components of the waste into silicon and aluminum raw materials for effective synthesis of molecular sieves. These methods are cumbersome and also increase energy consumption. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a method for preparing SSZ-13 molecular sieve. The present invention uses industrial perlite waste as raw material to synthesize a high value-added SSZ-13 molecular sieve product, and does not undergo activation pretreatment, but is hydrothermally synthesized in one step, with simple steps.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing SSZ-13 molecular sieve, comprising the following steps:
[0007] The template, alkali source, water, industrial perlite waste and silicon source are mixed to obtain a mixture; the alkali source is sodium hydroxide; the alkali source is calculated as Na2O, the industrial perlite waste is calculated as SiO2 and Al2O3, the silicon source is calculated as SiO2, and the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(2.31-3.85):(2.12-3.85):1692;
[0008] The mixture is subjected to hydrothermal crystallization to obtain SSZ-13 molecular sieve; the temperature of the hydrothermal crystallization is 160-170°C.
[0009] Preferably, the template is N,N,N-trimethyl-1-adamantyl ammonium hydroxide.
[0010] Preferably, the total mass content of SiO2 and Al2O3 in the industrial pearlite waste is greater than 89%.
[0011] Preferably, the silicon source comprises silica sol.
[0012] Preferably, the mixing method is:
[0013] The template, the alkali source and water are first mixed to obtain a first mixture;
[0014] The first mixture is mixed with industrial pearlite waste to obtain a second mixture;
[0015] The second mixture is mixed with a silicon source for a third time to obtain the mixture.
[0016] Preferably, the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(3.08-3.85):(2.69-3.85):1692.
[0017] Preferably, the hydrothermal crystallization time is 48 to 120 hours.
[0018] Preferably, the hydrothermal crystallization time is 72 hours.
[0019] Preferably, after the hydrothermal crystallization, the obtained crystallization liquid is subjected to solid-liquid separation, solid phase washing and drying in sequence.
[0020] Preferably, the SSZ-13 molecular sieve has a crystalline morphology.
[0021] The present invention provides a method for preparing SSZ-13 molecular sieve, comprising the following steps: mixing a template, an alkali source, water, industrial perlite waste and a silicon source to obtain a mixture; the alkali source is sodium hydroxide; the alkali source is calculated as Na2O, the industrial perlite waste is calculated as SiO2 and Al2O3, the silicon source is calculated as SiO2, and the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(2.31-3.85):(2.12-3.85):1692; the mixture is hydrothermally crystallized to obtain SSZ-13 molecular sieve; the temperature of the hydrothermal crystallization is 160-170°C. Compared with the prior art, the present invention has the following advantages:
[0022] Beneficial effects:
[0023] The present invention uses industrial perlite waste as raw material to synthesize zeolite molecular sieve, replacing pure chemical reagents, can solve the problem of processing and storage of industrial perlite waste, while reducing production costs, and obtains SSZ-13 molecular sieve products with high added value;
[0024] The present invention adopts a high crystallization temperature to promote the effective utilization of silicon and aluminum sources in industrial pearlite waste, and can hydrothermally synthesize SSZ-13 molecular sieve in one step without activation pretreatment, thereby simplifying the operation steps and greatly saving energy.
[0025] The invention can synthesize SSZ-13 molecular sieve with good crystallinity and purity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD diagram of the molecular sieves prepared in the examples and comparative examples;
[0027] Figure 2 The SEM electron microscope images of the SSZ-13 molecular sieves prepared in Examples 1 to 5 are as follows: Figure 2 A1, A2, A3, A4 and A5 correspond to the SSZ-13 molecular sieve products A1, A2, A3, A4 and A5 prepared in the examples respectively. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing SSZ-13 molecular sieve, comprising the following steps:
[0029] The template, alkali source, water, industrial perlite waste and silicon source are mixed to obtain a mixture; the alkali source is sodium hydroxide; the alkali source is calculated as Na2O, the industrial perlite waste is calculated as SiO2 and Al2O3, the silicon source is calculated as SiO2, and the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(2.31-3.85):(2.12-3.85):1692;
[0030] The mixture is subjected to hydrothermal crystallization to obtain SSZ-13 molecular sieve; the temperature of the hydrothermal crystallization is 160-170°C.
[0031] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0032] The invention mixes a template, an alkali source, water, industrial pearlite waste and a silicon source to obtain a mixture.
[0033] In the present invention, the template is preferably N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH). In the embodiment of the present invention, the template is specifically added in the form of a 25wt% aqueous solution. In the present invention, the alkali source is sodium hydroxide; the silicon source preferably includes silica sol. In the present invention, the industrial perlite waste is waste formed in the process of producing expanded perlite, when some perlite powders cannot expand at high temperatures due to their small grain size (below 60 mesh); the main components of the industrial perlite waste are quartz and alumina. In the present invention, the total mass content of SiO2 and Al2O3 in the industrial perlite waste is preferably greater than 89%.
[0034] In the present invention, the alkali source is calculated as Na2O, the industrial perlite waste is calculated as SiO2 and Al2O3, the silicon source is calculated as SiO2, and the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(2.31-3.85):(2.12-3.85):1692, preferably (20-25):1:(3.08-3.85):(2.69-3.85):1692. In the embodiment of the present invention, the industrial perlite waste used is measured by X-ray fluorescence spectroscopy for element content, and the SiO2 content is 76.1wt% and the Al2O3 content is 13.5wt% converted to the molar ratio. The present invention controls the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture within the above range, and can more effectively utilize the silicon and aluminum components in the industrial perlite waste to achieve the preparation of SSZ-13 molecular sieve.
[0035] In the present invention, the mixing method is preferably:
[0036] The template, the alkali source and water are first mixed to obtain a first mixture;
[0037] The first mixture is mixed with industrial pearlite waste to obtain a second mixture;
[0038] The second mixture is mixed with a silicon source for a third time to obtain the mixture.
[0039] The present invention preferably adds the template and the alkali source into water for the first mixing. The present invention preferably cools the first mixture to room temperature and then adds industrial perlite waste thereto for the second mixing. The present invention preferably adds a silicon source to the second mixture (suspension) for the third mixing. In the present invention, the first mixing, the second mixing and the third mixing are preferably stirred and mixed at room temperature, i.e., no additional heating is required, and the stirring and mixing is based on stirring the components uniformly.
[0040] The present invention adopts the above-mentioned mixing method, firstly, the template agent and the alkali source (together serving as a structure directing agent) are evenly mixed, and then the silicon source and the aluminum source are added to make the reaction more complete.
[0041] After obtaining the mixture, the present invention performs hydrothermal crystallization on the mixture to obtain SSZ-13 molecular sieve. In the present invention, the temperature of the hydrothermal crystallization is 160-170°C; the time of the hydrothermal crystallization is preferably 48-120h, more preferably 72h. The present invention preferably transfers the mixture to a stainless steel reactor with a polytetrafluoroethylene liner for the hydrothermal crystallization. The present invention adopts a high crystallization temperature, which can promote the effective utilization of silicon and aluminum sources in industrial perlite waste, and can hydrothermally synthesize SSZ-13 molecular sieves in one step without activation pre-treatment. Compared with the acid activation, alkali activation or high-temperature calcination pre-treatment steps widely used in solid waste zeolite, the present invention simplifies the operation steps and greatly saves energy.
[0042] After the hydrothermal crystallization, the present invention also preferably sequentially performs solid-liquid separation, solid phase washing and drying on the obtained crystallization liquid to obtain SSZ-13 molecular sieve. The present invention has no special requirements for the solid-liquid separation method, and a solid-liquid separation method well known to those skilled in the art can be used, such as filtration. In the present invention, the washing is preferably water washing, and the pH value of the product after the washing is preferably 7 to 10, more preferably 9. The present invention has no special requirements for the drying temperature. In an embodiment of the present invention, the drying temperature is 75°C and the time is 24h.
[0043] In the present invention, the SSZ-13 molecular sieve has a crystalline morphology.
[0044] The topological structure of SSZ-13 molecular sieve is CHA. CHA molecular sieve is composed of composite building units (CBUs) d6r and cha cages, and has a three-dimensional pore structure. The pore diameter of CHA molecular sieve in the (001) direction is It is a typical octahedral small pore molecular sieve. Among them, CHA molecular sieve with silicon-aluminum ratio greater than or equal to 2.5 is generally called SSZ-13 molecular sieve.
[0045] The invention provides a new method for obtaining SSZ-13 molecular sieve by hydrothermal synthesis at a certain temperature using untreated industrial pearlite waste as raw material. The obtained molecular sieve has a crystal morphology, high crystallinity and purity.
[0046] In order to further illustrate the present invention, the preparation method of the SSZ-13 molecular sieve provided by the present invention is described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0047] Example 1
[0048] The SSZ-13 molecular sieve is prepared from industrial perlite waste as raw material. The steps are as follows:
[0049] (1) Add 0.523 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH) aqueous solution (mass fraction 25%) and 0.042 g of sodium hydroxide to 6.1 mL of water and stir well.
[0050] (2) After the solution obtained in step (1) was cooled to room temperature, 0.174 g of industrial perlite waste was added and stirred for 3 h.
[0051] (3) Add 0.709 g of silica sol (SiO2 mass fraction is 30%) to the suspension obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25SiO2:Al2O3:2.31Na2O:2.69TMAdaOH:1692H2O.
[0052] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 170° C. and a crystallization time of 72 h.
[0053] (5) The crystallized product was collected by filtration, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain a SSZ-13 molecular sieve product, which was recorded as product A1.
[0054] XRD test was performed on product A1. Figure 1 Curve A1 in the figure corresponds to the XRD test result of product A1. It can be seen that curve A1 is consistent with the standard spectrum, is a pure phase, and has a high degree of crystallinity.
[0055] The SEM electron microscope test of product A1 shows the following results: Figure 2 A1 in the figure shows that the product has a crystalline morphology.
[0056] Example 2
[0057] The SSZ-13 molecular sieve is prepared from industrial perlite waste as raw material. The steps are as follows:
[0058] (1) Add 0.523 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.057 g of sodium hydroxide to 6.1 mL of water and stir evenly.
[0059] (2) After the solution obtained in step (1) was cooled to room temperature, 0.174 g of industrial perlite waste was added and stirred for 3 h.
[0060] (3) Add 0.709 g of silica sol (SiO2 mass fraction is 30%) to the suspension obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25SiO2:Al2O3:3.08Na2O:2.69TMAdaOH:1692H2O.
[0061] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 170° C. and a crystallization time of 72 h.
[0062] (5) The crystallized product was collected by filtration, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain a SSZ-13 molecular sieve product, which was recorded as product A2.
[0063] XRD test was performed on product A2. Figure 1 Curve A2 in the middle corresponds to the XRD test result of product A2. It can be seen that curve A2 is consistent with the standard spectrum and is a pure phase.
[0064] The SEM electron microscope test of product A2 shows the following results: Figure 2 A2 in the figure shows that the product has a crystalline morphology.
[0065] Example 3
[0066] The SSZ-13 molecular sieve is prepared from industrial perlite waste as raw material. The steps are as follows:
[0067] (1) Add 0.411 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.071 g of sodium hydroxide to 6.2 mL of water and stir evenly.
[0068] (2) After the solution obtained in step (1) was cooled to room temperature, 0.174 g of industrial perlite waste was added and stirred for 3 h.
[0069] (3) Add 0.709 g of silica sol (SiO2 mass fraction is 30%) to the suspension obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25SiO2:Al2O3:3.85Na2O:2.12TMAdaOH:1692H2O.
[0070] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 170° C. and a crystallization time of 72 h.
[0071] (5) The crystallized product was collected by filtration, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain a SSZ-13 molecular sieve product, which was recorded as product A3.
[0072] XRD test was performed on product A3. Figure 1 Curve A3 in the middle corresponds to the XRD test result of product A3. It can be seen that curve A3 is consistent with the standard spectrum and is a pure phase.
[0073] The SEM electron microscope test of product A3 shows the following results: Figure 2 A3 in the figure shows that the product has a crystalline morphology.
[0074] Example 4
[0075] The SSZ-13 molecular sieve is prepared from industrial perlite waste as raw material. The steps are as follows:
[0076] (1) Add 0.747 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.071 g of sodium hydroxide to 5.9 mL of water and stir evenly.
[0077] (2) After the solution obtained in step (1) was cooled to room temperature, 0.174 g of industrial perlite waste was added and stirred for 3 h.
[0078] (3) Add 0.709 g of silica sol (SiO2 mass fraction is 30%) to the suspension obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25SiO2:Al2O3:3.85Na2O:3.85TMAdaOH:1692H2O.
[0079] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, the crystallization temperature was 170° C., and the crystallization time was 72 h.
[0080] (5) The crystallized product was collected by filtering, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain a SSZ-13 molecular sieve product, which was recorded as product A4.
[0081] XRD test was performed on product A4. Figure 1 Curve A4 in the middle corresponds to the XRD test result of product A4. It can be seen that curve A4 is consistent with the standard spectrum and is a pure phase.
[0082] The SEM electron microscope test of product A4 shows the following results: Figure 2 A4 in the figure shows that the product has a crystalline morphology.
[0083] Example 5
[0084] The SSZ-13 molecular sieve is prepared from industrial perlite waste as raw material. The steps are as follows:
[0085] (1) Add 0.523 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.071 g of sodium hydroxide to 6.3 mL of water and stir evenly.
[0086] (2) After the solution obtained in step (1) was cooled to room temperature, 0.174 g of industrial perlite waste was added and stirred for 3 h.
[0087] (3) Add 0.479 g of silica sol (SiO2 mass fraction is 30%) to the suspension obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 20SiO2:Al2O3:3.85Na2O:2.69TMAdaOH:1692H2O.
[0088] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 170° C. and a crystallization time of 72 h.
[0089] (5) The crystallized product was collected by filtering, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 hours to obtain a SSZ-13 molecular sieve product, which was recorded as product A5.
[0090] XRD test was performed on product A5. Figure 1Curve A5 in the middle corresponds to the XRD test result of product A5. It can be seen that curve A5 is consistent with the standard spectrum and is a pure phase.
[0091] The SEM electron microscope test of product A5 shows the following results: Figure 2 A5 in the figure shows that the product has a crystalline morphology.
[0092] Comparative Example 1
[0093] (1) Add 0.358 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.044 g of sodium hydroxide to 5.1 mL of water and stir evenly.
[0094] (2) After the solution obtained in step (1) is cooled to room temperature, 0.043 g of sodium aluminate is added and stirred for 3 h.
[0095] (3) Add 1 g of silica sol (SiO2 mass fraction is 30%) to the solution obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25SiO2:Al2O3:3.85Na2O:2.12TMAdaOH:1692H2O.
[0096] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 170° C. and a crystallization time of 72 h.
[0097] (5) The crystallized product was collected by filtration, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain product B1.
[0098] XRD test was performed on product B1. Figure 1 The middle curve B1 corresponds to the XRD test result of product B1, and it can be seen that curve B1 is an amorphous substance.
[0099] Comparative Example 2
[0100] (1) Add 0.358 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.044 g of sodium hydroxide to 5.4 mL of water and stir evenly.
[0101] (2) After the solution obtained in step (1) is cooled to room temperature, 0.043 g of sodium aluminate is added and stirred for 3 h.
[0102] (3) Add 0.75 g of silica sol (AS-40) to the solution obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25 SiO2:Al2O3:3.85 Na2O:2.12 TMAdaOH:1692 H2O.
[0103] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 170° C. and a crystallization time of 72 h.
[0104] (5) The crystallized product was collected by filtration, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain product B2.
[0105] XRD test was performed on product B2. Figure 1 The middle curve B2 corresponds to the XRD test result of product B2, and it can be seen that curve B2 is an amorphous substance.
[0106] Comparative Example 3
[0107] (1) Add 0.411 g of TMAdaOH aqueous solution (mass fraction 25%) and 0.071 g of sodium hydroxide to 6.2 mL of water and stir evenly.
[0108] (2) After the solution obtained in step (1) was cooled to room temperature, 0.174 g of industrial perlite waste was added and stirred for 3 h.
[0109] (3) Add 0.709 g of silica sol (SiO2 mass fraction is 30%) to the suspension obtained in step (2), stir evenly at room temperature for 1 h, and the molar ratio of the active ingredients in the resulting mixture is 25SiO2:Al2O3:3.85Na2O:2.12TMAdaOH:1692H2O.
[0110] (4) The mixture obtained in step (3) was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal crystallization at a crystallization temperature of 120° C. and a crystallization time of 72 h.
[0111] (5) The crystallized product was collected by filtration, washing (washing until the product pH is 9) and drying at a drying temperature of 75° C. for 24 h to obtain product B3.
[0112] XRD test was performed on product B3. Figure 1 The middle curve B3 corresponds to the XRD test result of product B3, and it can be seen that curve B3 is an amorphous substance.
[0113] As can be seen from the above examples, the present invention provides a simple method for synthesizing SSZ-13 molecular sieve using industrial perlite waste as raw material, and realizes the first preparation of SSZ-13 molecular sieve using industrial perlite waste as raw material. Under the premise of ensuring product purity and crystallinity, the pre-treatment step of industrial perlite waste is omitted, the process flow is simplified, and energy consumption is reduced. The present invention realizes the resource utilization of industrial perlite waste, reduces the preparation cost of zeolite molecular sieve, and synthesizes high-crystallinity zeolite molecular sieve materials.
[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing SSZ-13 molecular sieve, characterized in that: The following steps are involved: The template, alkali source, water, industrial perlite waste and silicon source are mixed to obtain a mixture; the alkali source is sodium hydroxide; the alkali source is calculated as Na2O, the industrial perlite waste is calculated as SiO2 and Al2O3, the silicon source is calculated as SiO2, and the molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(2.31-3.85):(2.12-3.85):1692; The mixture is subjected to hydrothermal crystallization to obtain SSZ-13 molecular sieve; the temperature of the hydrothermal crystallization is 160-170°C.
2. The preparation method according to claim 1, characterized in that: The template agent is N,N,N-trimethyl-1-adamantyl ammonium hydroxide.
3. The preparation method according to claim 1, characterized in that: The total mass content of SiO2 and Al2O3 in the industrial pearlite waste is greater than 89%.
4. The preparation method according to claim 1, characterized in that: The silicon source includes silica sol.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mixing method is: The template, the alkali source and water are first mixed to obtain a first mixture; The first mixture is mixed with industrial pearlite waste to obtain a second mixture; The second mixture is mixed with a silicon source for a third time to obtain the mixture.
6. The method according to claim 1, characterized in that The molar ratio of SiO2, Al2O3, Na2O, template and water in the mixture is (20-25):1:(3.08-3.85):(2.69-3.85):1692.
7. The method according to claim 1, characterized in that The hydrothermal crystallization time is 48 to 120 hours.
8. The method according to claim 1 or 7, characterized in that: The hydrothermal crystallization time is 72h.
9. The method according to claim 1, characterized in that: After the hydrothermal crystallization, the obtained crystallization liquid is sequentially subjected to solid-liquid separation, solid phase washing and drying.
10. The method according to claim 1, characterized in that The SSZ-13 molecular sieve has a crystalline morphology.
Citation Information
Patent Citations
Hierarchical pore-containing small-grain SSZ-13 molecular sieve and synthesis method thereof
CN111056561A
Method for preparing ZSM-5 molecular sieve from perlite waste and ZSM-5 molecular sieve prepared by method
CN114455603A
Aluminum germanium silicate molecular sieve SSZ-121, synthesis and use thereof
CN115667143A
Method for synthesizing high-silicon SSZ-13 molecular sieve by crystal transformation of strontium feldspar
CN116409794A
Method for producing zeolite using hydrous aluminum sludge discharged in aluminum production process
JP2006044978A
Cited By
Method for preparing SSZ-13 zeolite molecular sieve from dried drilling mud and application of SSZ-13 zeolite molecular sieve
CN122035896A